Assessing the effect of electronic word of mouth and firm strategy on business performance as perceived by selected online sellers - Asis, Angela Ann Marie Calopez (Animo Repository, 2022)
The main focus of this study, which was conducted by the researchers, was to identify the effects of electronic word of mouth and firm strategy on the firm performance of selected online businesses in the Philippines. The research approach is quantitative, descriptive, correlational, and causal-explanatory because the purpose of this study is to characterize and portray the participants' views and opinions. Mean response scores and standard deviations were used to determine the extent of electronic word of mouth, business performance, and firm strategy of online businesses in Metro Manila. The researchers also analyzed Pearson's correlation coefficient to see if there was a link between electronic word of mouth and firm strategy and online business performance in Metro Manila. Finally, the effect of electronic word of mouth and firm strategy on the firm performance of online businesses in Metro Manila was investigated using the p-value and significance f methods. A survey of 100 online sellers in Metro Manila was undertaken. For their businesses, these respondents use digital markets. The study's findings reveal the survey's and comparable research’s similarities and differences. That said, electronic word of mouth and firm strategy may not have as big of an impact on the firm performance of online businesses which is in contrast with the findings of previous research on similar studies. This is for a variety of reasons, and the researchers offered suggestions on how aspiring entrepreneurs, online businesses, other businesses, academe, and future researchers can continue to use electronic word of mouth and firm strategy in their businesses, maximize the knowledge gained from this study, and, most importantly, take this study forward.